2003
DOI: 10.1029/2002gl016349
|View full text |Cite
|
Sign up to set email alerts
|

Record heavy Asian dust in Beijing in 2002: Observations and model analysis of recent events

Abstract: A record heavy Yellow Sand event was observed on 20 March in Beijing. This event was unusual because the wind speed was low and the dust concentration was extremely high at the dust front. Observations with a polarization lidar, an optical particle counter, and a high‐volume sampler were performed throughout the event in Beijing. The visibility derived from the lidar data was 650 m, and the total suspended particle concentration was 11 mg/m3 at the peak. Chemical transport model analysis revealed that the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
157
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(161 citation statements)
references
References 15 publications
3
157
0
1
Order By: Relevance
“…We categorized the kosa concentration into five grades as follows: Grade 1, equated to 0 μg/m 3 ; Grade 2, 0-10 μg/m 3 ; Grade 3, 10-30 μg/m 3 ; Grade 4, 30-100 μg/m 3 ; and Grade 5, over 100 μg/m 3 . It was reported that the standard threshold of the dust concentration for an Asian dust day was 100 μg/m 3 (Sugimoto et al, 2003). Besides these days, the typical kosa days were identified as increase in the LIDAR signal of more than 30μg/m 3 in this study period.…”
Section: Discussionmentioning
confidence: 86%
“…We categorized the kosa concentration into five grades as follows: Grade 1, equated to 0 μg/m 3 ; Grade 2, 0-10 μg/m 3 ; Grade 3, 10-30 μg/m 3 ; Grade 4, 30-100 μg/m 3 ; and Grade 5, over 100 μg/m 3 . It was reported that the standard threshold of the dust concentration for an Asian dust day was 100 μg/m 3 (Sugimoto et al, 2003). Besides these days, the typical kosa days were identified as increase in the LIDAR signal of more than 30μg/m 3 in this study period.…”
Section: Discussionmentioning
confidence: 86%
“…The LIDAR system distinguishes between mineral dust particles, including Asian dust, and other spherical particles by identifying differences in the shapes of the particles (Sugimoto et al, 2003). Recently, some epidemiological studies have used LIDAR data to evaluate the health effects of Asian dust.…”
Section: Discussionmentioning
confidence: 99%
“…We averaged 24 h data, obtained from the atmosphere 1 km above the ground at the Toyama observation station (Imizu City, Toyama Prefecture, Japan) which is approximately 40 km east of Kanazawa City. The standard threshold of the dust extinction coefficient for a Asian dust day was 0.1/km (Sugimoto et al, 2003). The Japan Meteorological Agency identifies a Asian dust day (the occurrence of a Asian dust event)…”
Section: Definition Of the Asian Dust And Non-asian Dust Periodsmentioning
confidence: 99%
“…Because the depolarization ratio is available, the lidar data can provide us the information on non-spherical particles such as dust particles (e.g., Shimizu et al 2004;Osada et al 2011;Yasunari et al 2016). We use the calculated dust and spherical extinction coefficients of the lidar data (Sugimoto et al 2003;Shimizu et al 2004) at Takikawa to confirm Kosa (dust) transports there (also see SI Text).…”
Section: Introductionmentioning
confidence: 99%